The Search for Truth: An Analysis of the Derivational Affixes Found in the Selected Poems of Fernando A. Bernardo’s The Silent Voice of Your Soul - Kay T Juanillo; Ann Mellene Capuy Fernandico (STAIN Sultan Abdurrahman Kepulauan Riau, 2022)
One of the most important components of language is Vocabulary, a set of words or the combinations of symbols, signs, or letters that have evolved to identify things and ideas. It is an important component of language and language learning as the lack of it hampers a person’s ability to comprehend and communicate effectively. This research analyzes the derivational affixes found in the selected poems of Fernando A. Bernardo in his book entitled The Silent Voice of Your Soul. This research is important as it can help enrich and widen the vocabulary of readers by helping them identify derivational affixes and the functions of these affixes. This study will also help the readers understand how certain words change their word class and meaning as different affixes are added to them Descriptive Qualitative Content Analysis was used to analyze thoroughly the derivational affixes found in the poems. Based on the analysis, there are a total of fifty-five (55) words with derivational affixes found in the poem. Twenty-five (25) words have noun-forming affixes which consist of -ance, -ence, -ity, -ness, -ion, and -or. Sixteen (16) words have adjective-forming affixes which consist of -ty, -ful, -less, -ous, -al, -ry, -tial, and -ed. Eight (8) words in the poems consist of verb-forming affixes such as un-, dis-, ate, and -ing. Lastly, six (6) words from the poems are formed with the adverb-forming affix -ly. Through understanding the different words used, the readers can improve their vocabulary and understanding of the language and literary texts.